2017
DOI: 10.1007/s12011-017-1000-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum Level of Zinc and Copper in Sudanese Women with Polycystic Ovarian Syndrome

Abstract: The study aimed to evaluate the serum level of zinc and copper in women with polycystic ovarian syndrome (PCOS). A case-control study was conducted at Saad Abualila infertility center (Khartoum, Sudan). The cases were women who had a PCOS based on Rotterdam criteria. The controls were infertile women with no evidence of PCOS. The socio-demographic characteristics and medical history data were gathered using questionnaires. Zinc and copper levels were measured using atomic absorption spectrophotometer. While th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…It has been reported that Mg is central in the cell cycle, and that its deficiency is an important conditioner in precancerous cell transformation. On the other hand, at increased levels, magnesium can cause damage to the brain, liver, kidneys, and the developing foetus 31 In the current study, there were a significantly (P < 0.01) increased in level of Cu and significantly (P < 0.01) decreased in level of Zn in obese and non obese PCOS patients with primary and secondary, with compared to control. On the other hand, there was no significant change (P>0.05) when comparing the level of Cu and Zn between primary and secondary (in both obese and nonobese PCOS patients).…”
Section: Discussionsupporting
confidence: 39%
“…It has been reported that Mg is central in the cell cycle, and that its deficiency is an important conditioner in precancerous cell transformation. On the other hand, at increased levels, magnesium can cause damage to the brain, liver, kidneys, and the developing foetus 31 In the current study, there were a significantly (P < 0.01) increased in level of Cu and significantly (P < 0.01) decreased in level of Zn in obese and non obese PCOS patients with primary and secondary, with compared to control. On the other hand, there was no significant change (P>0.05) when comparing the level of Cu and Zn between primary and secondary (in both obese and nonobese PCOS patients).…”
Section: Discussionsupporting
confidence: 39%
“…The study also revealed that there is no significant difference in serum copper concentration between healthy and PCOS women. Although there were three previous studies that showed higher copper levels in PCOS group than healthy group 18 -20 , a recent study 22 showed no significant difference in copper levels as well between the two groups.…”
Section: Discussionmentioning
confidence: 81%
“…Zinc is considered as one of the cofactors of antioxidant enzymes, such as catalase (CAT) and SOD1 [72]. While the studies described in this review did not show any changes in SOD1 activity, changes in serum zinc concentration, serum copper concentration, as well as Cu/Zn ratio were observed in woman with PCOS [29,47,51]. Higher generation of ROS is postulated as one of the factors involved in the etiopathogenesis of PCOS [73], because it results in lipid peroxidation and damage of cell membrane lipids [48].…”
Section: Zinc and Polycystic Ovary Syndrome (Pcos)mentioning
confidence: 78%